Shear-force-dominated dual-drive planetary ball milling for the scalable production of graphene and its electrocatalytic application with Pd nanostructures. Issue 24 (18th February 2016) - Kumar, G. Rajendra; Jayasankar, K.; Das, Sushanta K.; Dash, Tapan; Dash, Ajit; Jena, Bikash Kumar; Mishra, Barada Kanta
Abstract : We employed simple shear-force-dominated planetary ball milling to prepare graphene on a large scale (200 g per cycle) with less structural defects. Abstract : The exceptional properties of graphene-based derivatives have governed numerous research fields in recent years. The scaled up and reliable production of high-quality graphene is still a challenging task. This work presents an efficient and low-cost approach for the mass production of high-quality graphene (50 g scale batch) through the dual-drive planetary ball milling of graphite with a dicarboxylic acid. The dimensional changes of graphite were determined from the diffraction pattern of the (002) plane at different milling times and the unique signature of graphene noticed in the Raman spectra. Transmission electron microscopy clearly revealed the existence of single and bilayer graphene sheets. Non-destructive exfoliation was evidenced by the surface binding states of the C 1s core level spectra. The as-synthesized graphene was utilized as the catalytic support for formic acid fuel cell applications. Graphene supported palladium nanocomposites were prepared, and the electrocatalytic activity towards formic acid oxidation was explored. The cyclic voltammogram of the graphene–palladium nanocomposite reveals that the onset potential for formic acid oxidation is −0.1 V with a prominent oxidation peak at 0.263 V.